AMIGO2, a toolbox for dynamic modeling, optimization and control in systems biology - Balsa-Canto, Eva; Henriques, David; Gábor, Attila; Banga, Julio R. (Bioinformatics (Oxford, England), 2016)
Motivation: Many problems of interest in dynamic modeling and control of biological systems can be posed as non-linear optimization problems subject to algebraic and dynamic constraints. In the context of modeling, this is the case of, e.g. parameter estimation, optimal experimental design and dynamic flux balance analysis. In the context of control, model-based metabolic engineering or drug dose optimization problems can be formulated as (multi-objective) optimal control problems. Finding a solution to those problems is a very challenging task which requires advanced numerical methods. Results: This work presents the AMIGO2 toolbox: the first multiplatform software tool that automatizes the solution of all those problems, offering a suite of state-of-the-art (multi-objective) global optimizers and advanced simulation approaches. Availability and Implementation: The toolbox and its documentation are available at: sites.google.com/site/amigo2toolbox . Contact:  ebalsa@iim.csic.es Supplementary information:  Supplementary data are available at Bioinformatics online.